THE NUTRITIVE AND ECONOMIC EFFECTS OF AEROBIC TREATMENT OF SOLID MANURE - Radivojević, Dušan; Ivanović, Sanjin; Radojičić, Dušan; Koprivica, Ranko; Božić, Steva (Economics of Agriculture, 2012)
The aerobic treatment of solid manure increases the content of total and easily available amounts of N, P2O5, K2O by 3.76 times on average in comparison with raw solid manure, and makes the maturation time eight time as short, which is significant for several reasons. In this paper, we showed that the price of the substitution of compost derived from aerobic processing is 4.24 times as high in comparison with the price of the substitution of burnt manure derived through anaerobic processing. By applying different dynamic methods for the assessment of investments, a fact was established that investing in the purchase of a machine for the aerobic processing of manure is economically justified and financially acceptable for farms with 19 and more cows.